A Study on Pyrolysis of Pretreated Automotive Shredder Residue—Thermochemical Calculations and Experimental Work - Vijayan, Sandhya Kuruvalan; Kibria, Mahmud Arman; Bhattacharya, Sankar (Frontiers in Sustainability, 2022)
The Automotive Shredder Residue (ASR) is generated as an inevitable waste after the shredding process of the end-of-life vehicles. Typically, the ASR ends up in a landfill in the absence of any existing processing options. The ASR comprises rubber (20%), wood (2-5%), plastics (19-35%), textile (10-40%), metals (8%), and other unknown materials such as paint and (glass (10%), which can be recycled and reused. Given these attributes, the ASR is a potential feedstock for energy production and metal recovery. In this study, ASR has first pretreated ASR because untreated ASR ( as received) is fluffy and heterogeneous and, therefore, is difficult to feed into a reactor. Subsequently, the pyrolysis process was conducted with this pretreated ASR for energy recovery. From the thermochemical calculations, an optimized temperature of 500 °C was chosen for pyrolysis of pretreated ASR to ensure that metals would not be further oxidized and polymers could be separated from the metals in the form of volatile gases, oil, and char. Bench-scale pyrolysis tests were conducted on an integrated continuous stirred tank reactor- distillation column pyrolysis system. The product gas composition had hydrogen and methane content of 30% and 26 % (v/v), respectively contributing to the heating value of the gas obtained. The pyrolysis oil was further distilled using fractional distillation apparatus for gasoline and diesel-grade products. The physicochemical characterization of the pretreated ASR pyrolysis oil and its distillates was also carried out. The thermochemical equilibrium predictions showed a similar trend with the experimental pyrolysis results. In addition, the residual char analysis indicated the presence of a significant amount of metals - silicon, titanium, aluminum, and iron. Thus, This study work generated information on processing for recycling ASRpretreated ASR waste for energy for the production of fuel and insights on metals recovery that can be recovered from the residual pyrolysis char. to avoid their disposal in landfills.